a) $(1 + x)(1 - x)(1 + x^2) = (1 - x^2)(1 + x^2) = 1 - x^4$
б) $(a - 2)(a + 2)(a^2 + 4) = (a^2 - 4)(a^2 + 4) = a^4 - 16$
в) $(m + n)(n - m)(m^2 + n^2) = -(m+n)(m-n)(m^2+n^2) = -(m^2-n^2)(m^2+n^2) = -(m^4-n^4)=n^4-m^4$
г) $(3 - p)(3 + p)(9 + p^2) = (9 - p^2)(9 + p^2) = 81 - p^4$
д) $(x + 2)(4 - x^2)(x - 2) = -(x+2)(x-2)(x^2-4)=-(x^2-4)(x^2-4)=-(x^2-4)^2=-(x^4-8x^2+16)=-x^4+8x^2-16$
ж) $(a - b)(a - b)(a + b)(a + b) = (a-b)^2(a+b)^2 = ((a-b)(a+b))^2=(a^2-b^2)^2=a^4-2a^2b^2+b^4$
е) $(p + 1)(p + 2)(p^2 + 4)(p^2 + 1)$ - это выражение не является формулой сокращенного умножения и не упрощается к простой форме.
Ответы:
a) $1 - x^4$
б) $a^4 - 16$
в) $n^4 - m^4$
г) $81 - p^4$
д) $-x^4+8x^2-16$
ж) $a^4 - 2a^2b^2 + b^4$
e) $(p + 1)(p + 2)(p^2 + 4)(p^2 + 1)$